THE APPLICATION OF TIME VALUE OF MONEY ON FAMILY GATHERING COSTS AT WEDDINGS - Beatrix Yunarti Manehat; Yolinda Yanti Sonbay; Yohanes Pemandi Lian (SEAN Institute, 2023)
This study aims to photograph people's awareness of the application of the Time Value Of Money concept to the cost of family gatherings during wedding preparations in East Nusa Tenggara Province. The research method used is a qualitative method. Sample selection using convenience sampling method. Data analysis using Husserl phenomenology. The results show that the concept of time value of money applies in family gatherings for wedding preparations. Family gathering is a place to unite the family. The perpetrators realized that the money collected at this time (at family gatherings) had a different value from previous years and realized that the value of money given today was more valuable because it helped the needs of the family of the organizers. Family gathering does involve money as a store of value, but what is seen is not the amount of money given but the value of solidarity and the desire to launch a marriage. Money only symbolizes the high level of love and support between family members, friends and relatives. The families involved are aware of changes in the value of money from time to time. At family gatherings, the importance of the present value of money and Preference Present Consumption to Future Consumption as part of time value of money is also applied.